Dead migrants in the Mediterranean: genetic analysis of bone samples exposed to seawater. (November 2022) - Bertolini, Emilie; Grignani, Pierangela; Bertoglio, Barbara; Marrubini, Giorgio; Mazzarelli, Debora; Lucheschi, Stanilla; Bosetti, Alessandro; Fattorini, Paolo; Cattaneo, Cristina; Previderé, Carlo
Abstract: In April 2015, a fishing boat that departed from Libya with about 1, 000 migrants on board sank in the Mediterranean Sea. Most of the migrants were packed in the hull of the boat and drowned in the shipwreck. After fifteen months, the ship was recovered from the seabed and brought to a Sicilian naval area for forensic investigations. Skeletal remains belonging to more than 700 people were retrieved. A selected sample composed of 80 victims was considered in order to evaluate the possibility of achieving genetic profiles useful for a positive identification from these challenging specimens. The molecular features of the DNA recovered from a significant number of real casework samples exposed to seawater for long periods of time were described for the first time. Three different DNA extraction protocols and three different commercial kits were employed in order to generate genetic profiles based on the characterization of 21 autosomal STR loci. The combination of multiple DNA extractions and the cross-checking of multiple PCR amplifications with different kits allowed to obtain reliable genetic profiles characterized by at least 16 STR markers in more than 70% of the samples. The factors that could have affected the different quality of the genetic profiles were investigated and the bone preservation was examined through microscopic and macroscopic analyses. The approach presented in this study could be useful in the management of the genetic analysis of bone samples collected in other similar DVI scenarios. The genetic profiles recovered from the bone samples will be compared in kinship analysis to putative relatives of the victims collected in Africa in order to obtain positive identifications. Highlights: Bone samples belonging to dead migrants in the Mediterranean were analysed. An approach involving multiple DNA extraction methods and STR kits was applied. Reliable genetic profiles (≥16 STRs) were obtained for more than 70 % of the samples. Factors influencing the quality of the genetic profiles were evaluated.